[San Luis Obispo residence and High School Hill?] (1913)
Yard of a San Luis Obispo residence. In distance is High School Hill, with the letters CPS visible. For a time, the San Luis Obispo High School and the California Polytechnic School students had a rivalry where they would mark their opponent's hillside with their initials. Newspaper reports cover this event in 1913 and 1914. There may be a large unidentified falling object in center of photograph. See also image ua-pho_00001408 https://digital.lib.calpoly.edu/rekl-11701, which may be a photo of the same house facing another direction.